Antibacterial Activity of The Galls of Quercus infectoria - D.F, Basri; F.S, Ha,; Zin N, Mohamed; I, Jantan (Malaysian Journal of Science, 2005)
In this study, the galls of Quercus infectoria were finely ground and extracted successively with petroleum ether, ethyl acetate and ethanol. Successive extraction with acetone followed by methanol was also carried out in addition to preparation of aqueous extraction. The extracts were screened against 3 Gram-positive bacteria (Staphylococcus aureus ATCC 25923, S. epidermidis and Bacillus subtilis) and 4 Gram-negative bacteria (Escherichia coli O157:H7, Salmonella typhimurium NCTC 74, S. enteritidis NCTC 5188 and Pseudomonas aeroginosa ATCC 27853). The antibacterial testing was carried out by using the disc diffusion method. All extracts showed moderate activity against all the Gram-positive bacteria; methanol extract exhibiting the highest inhibition zone diameter of 15.84 mm Ã‚Â± 0.56 mm against Staphylococcus aureus. Among the Gram-negative bacteria tested, E. coli O157:H7 appeared to be the most resistant towards the extracts.